Soviet Union Spionage Arrest In Indonesia 1982 - Ukasyah, Syifa Surya; Puji, Rully Putri Nirmala; Triyanto, Jefri Rieski; Prasetyo, Guruh; Soepeno, Bambang (History Education, University of Jember, 2023)
The purpose of this study is to analyze the events of the Soviet Union's espionage arrest in Indonesia in 1982. The formulation of the problem in this research is (1) The Soviet Union's Efforts to Steal Indonesian Maritime Data, (2) The Process of the Soviet Union's Intelligence Arrests for Espionage in Indonesia, and (3) the Settlement of the Soviet Union's Espionage Case in Indonesia in 1982. The method used is historical methodology which includes five selection steps including topics, heuristics, source criticism, interpretation and historiography. The Soviet Union's espionage arrest occurred in 1982 which was carried out by a task force codenamed Pantai, a joint effort between the State Intelligence Coordinating Agency (BAKIN) and a task force led by Brigadier General M.I Sutaryo. The cause of the Soviet Union's espionage arrest was an attempt to steal Indonesia's secret deep data regarding the condition, content and depth of the sea in the Lombok Strait and the Natuna Islands. The perpetrators of Soviet espionage who were caught by the Beach task force named Sergei Egorov and Alexander Finenko. The case settlement process was carried out by giving persona non-grata status and closing the Soviet Union's Aeroflot airline operating in Indonesia. Keywords: Espionage Arrest, Soviet Union Espionage, Data Theft